Development organisations facilitating women s access to finance - Dido Bashuna, Sabdiyo; Ongango, Mellyne (Technical Centre for Agricultural and Rural Cooperation, 2019)
Sabdiyo Dido Bashuna from CTA and Mellyne Ongango from AGRA explain how their respective organisations are working towards facilitating women s access to finance in agriculture